The use of alpha-adrenergic antagonists in pediatric nephrolithiasis: a systematic review - Haddad, Firas; Farhat, Walid A.; Cannon, Shannon (Frontiers in Pediatrics, 2024)
Objective: To evaluate existing clinical evidence for the efficacy of alpha blockers in the management of pediatric stone disease.Methods: We conducted a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Cohort and randomized control trials of patients less than 18 years old with kidney stones managed with alpha-adrenergic antagonists were included. Outcomes included stone expulsion time, stone passage rate, mean number of pain episodes, and mean need for analgesics. We performed data extraction of the selected articles, and results were assimilated and synthesized qualitatively. Data extraction and risk of bias assessment was conducted by two independent reviewers. Results: Of 257 relevant studies, 9 studies with 1039 patients were included. Six studies measured stone expulsion time, with 5 studies noting statistically significant decreases in stone expulsion time for the treatment group compared to the control. Seven studies measured the stone expulsion rate, and 5 reported a statistically significant increased expulsion rate in the treatment group. Four studies reported a decrease in the mean number of pain episodes in the treatment group and two studies showed a decreased analgesic requirement compared to control. Two studies found alpha blockers not superior to watchful waiting after shock wave lithotripsy. Risk of bias was high in some studies, primarily due to incomplete reporting on methodology and study design.Conclusions: Alpha blockers are supported by a growing body of evidence to be effective against nephrolithiasis in children, however large-scale, well-designed studies are needed to confirm these findings.